Pyelonephritis in Early Children - I. L., Sharipov (American Journal of Biology and Natural Sciences, 2024)
The relevance of the topic is due to the high prevalence and frequent recurrence of this pathology. In this regard, timely diagnosis of acute pyelonephritis and adequate treatment will improve the prognosis of the disease and reduce the frequency of chronicity of the process.